Primary diffuse large B-cell lymphoma of orbit: A population-based analysis - Chen, Yu-Qing; Yue, Zi-Fan; Chen, Sai-Nan; Tong, Fei; Yang, Wei-Hua; Wei, Rui-Li (Frontiers in Medicine, 2022)
Objective: Primary orbital lymphoma (POL) accounts for an essential part of adult orbital malignancies. Nevertheless, it remains a relatively rare lymphoid malignancy, accounting for <1% of all non-Hodgkin’s lymphoma (NHL) cases. Orbital diffuse large B-cell lymphoma (DLBCL) is one of the most prevalent subtypes of POL that confers the worst outcomes. The prognostic determinants of orbital DLBCL remain unknown. Therefore, a retrospective analysis was conducted by investigating the Surveillance, Epidemiology, and End Results (SEER) database for independent predictive factors for the prognosis of orbital DLBCL. Materials and Methods: Using the SEER program, we acquired patient data including demographics, clinical characteristics, and treatment strategies. Our cohort included cases of primary orbital DLBCL diagnosed from 2000 to 2017. We conducted Kaplan-Meier analyses to visualize the overall survival (OS) and cause-specific survival (CSS). The Cox proportional hazard regression models were applied to assess the effects of these prognostic factors on OS and CSS. Results: The present cohort included 332 patients with orbital DLBCL. Age was the most impacted variable by orbital DLBCL. Three independent prognostic variables of orbital DLBCL were identified on diagnosis: advanced age, no radiation treatment, and late-stage (Stage IV). Moreover, patients who underwent chemotherapy demonstrated a greater OS when compared with those who did not. In orbital DLBCL, being unmarried was also a poor prognostic factor. Conclusion: The current study is the largest population-based case series of orbital DLBCL. The age at the time of diagnosis, marital status, absence of chemotherapy or radiotherapy, and tumor stage were all found to be correlated with worse prognosis.